Model Terpadu Pendekatan Direct Instruction-Komunikatif dalam Program Pelatihan Publikasi Karya Ilmiah: The Integrated Model of Direct Instruction–Communicative Approach in the Training Program of Scientific Work Publication - Simpun; Dina Mardiana; Kuswari; Ichyatul Afrom; Kristiana Natalina; Yeny Wulandari; Andre Kurniawan (Pusat Kajian Bahasa Daerah & Budaya, 2023)
The purpose of this qualitative-conceptual research is to describe a literature on the result of the development of an integrated model of the direct instruction and communicative approach. The integrated direct instruction-communicative approach is applied in a training program for publication of scientific papers in ICT-based or OJS-based in scientific journals for classroom teachers in Central Kalimantan Province. This activity was carried out in July 2023 and involved 30 classroom teachers from various primary schools in Central Kalimantan Province. The development model design of integrated approach between direct instruction and communicative approach used Borg and Gall Research and Development method covering to the third stage, namely product development. In its application, the integrated approach of direct instruction and communicative approach includes the modeling phase and the strategy of communicative competence. From the results of the integrated model development applied, it was found that the classroom teacher's knowledge and skill increased when evaluated, that is by obtaining an average score of 82 with a completion percentage of 91%. Thus, it can be concluded that the integrated approach of direct instruction and communicative approach is very relevant to be used in the training program of scientific paper publication for classroom teachers of primary schools in Central Kalimantan Province.